Numerical analysis of clamping pressure during carton clamp handling of heavyweight corrugated packages - Park, Jongmin; Kim, Jongsoon; Park, Jonghun; Horvath, Laszlo; Kim, Ghiseok (International Journal of Agricultural and Biological Engineering, 2017)
In order to determine the theoretical minimum clamping pressure required in carton clamp handling of heavyweight corrugated package (HCP) such as large packages or unitized agricultural product packages, a numerical model of clamping pressure was developed. To develop the model, the dynamic load factor was measured at the handling test course which was designed on the basis of actual handling environment of the target HCP. Also, the static-frictional coefficients between the HCPs and between the HCP and a rubber contact pad of carton clamp arm were analyzed. The main factors in the developed numerical model of clamping pressure were the handling load weight and the effective contact area of the carton clamp arm. In addition, field tests were performed to validate the theoretical minimum clamping pressure calculated from the model. Averaged slip distance from the single package and two packages handling was estimated as a 3.2 mm through field test, and it is expected that the 3.2 mm slip distance will be acceptable for a safe operation in the handling environment. The suggested analytical approach with the numerical model can be a useful means for estimating the clamping pressure of the carton clamps used to handle the HCP. Keywords: corrugated paperboard, heavyweight package, agricultural product packages, carton clamp, clamping pressure, dynamic load factor DOI: 10.25165/j.ijabe.20171005.2917 Citation: Park J, Kim J, Park J, Horvath L, Kim G. Numerical analysis of clamping pressure during carton clamp handling of heavyweight corrugated packages. Int J Agric & Biol Eng, 2017; 10(5): 25–34.